SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA TERBAIK DI EEC JOMBANG MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY - M. Hamzah Ulumuddin; Chamdan Mashuri (Fakultas Teknologi Informasi, 2025)
The selection of the best student is a routine agenda carried out by educational institutions as a form of appreciation for students who have superior achievements in various aspects. As applied at EEC Jombang, the best student selection process has been done manually by referring to the test score results. Therefore, it is necessary to have a web-based decision support system so that it can facilitate the selection of the best students in a more objective and structured manner. This research designs the system by applying the Multi Attribute Utility Theory (MAUT) method, because this method is able to handle various criteria and produce utility values for each alternative. The criteria in using the system include test scores, activeness, discipline, and attendance. The system is developed with the PHP programming language and utilizes MySQL as its database. The results of the application of the MAUT method show that the system is able to automatically calculate student preference scores based on predetermined criteria weights, as well as compile rankings to determine the students who are most deserving of the best title. The presence of this system makes the best student selection process more efficient, transparent, and accountable. Keywords: Decision Support System, Multi-Attribute Utility Theory, Top Students.